The The Use Of Code Switching and Code Mixing in English learning at Elementary School - Maftukhin Tukhin; Susilawati; Eline Rozaliya Winarto (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Muhammadiyah Cirebon, 2023)
Abstract Many people speak by switching or mixing the language they use in general with their mother tongue, especially in communicating with people who understand a different language. In the process of learning English, code switching and code mixing began to be used by teachers. In general, students who study formally in Indonesia, their first language is Indonesian and learn the second language only in the classroom. The use of code switching and code mixing in English learning at elementary schools has an impact on students' understanding of learning materials, as well as affecting their social aspects and language understanding. This study aims to find out how the use of code switching and code mixing in learning and the reasons why teachers use code switching and code mixing in English learning at elementary school. This study used descriptive qualitative methodology. This study used interviews and observations to obtain data. The research was conducted at SDQ AZZAMZAMI Talun. The findings of this study show that teachers do code switching and code mixing used by teachers alternately irregularly in carrying out the learning process at each general step of learning, namely, from the beginning of the opening, core activities to closing. The researcher also found that the reason teachers use language switching and language mixing are : a) Repitition b) Situation c) Restore student concentration d) Lake of vocabulary mastery e) Help students who were confused.